Силабічні форми у творчості східноукраїнських поетів 90-х років ХІХ ст. - Любімова, Оксана; Lyubimova, Oksana (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті розглянуто східноукраїнську поезію у зрізі метрики та ритміки. У сегменті монорозмірного складочисельного віршування превалювали 14-складовики, 6-складовики та 8-складові форми. Поміж різно¬розмірних форм домінували коломийковий 14-складовик зі схемою 8, 6, 8, 6 та 13-складовий силабічний вірш із двома варіантами схем – 8, 5, 8, 5 та 7, 6, 7, 6. Поети також вдалися до нерівноскладових невпо¬рядкованих силабічних віршів.The article deals with the East Ukrainian poetry in regards of metrics and rhythmics. The poets tested a vast array of syllabic metres over the mentioned decade. Metrical lines of fourteen, six and eight syllables dominated the segment of monometric syllabic-numerical structures (22,7 % of total amount of syllabic texts of the given time interval). The authors also resorted to «koltsovs’kyy» pentasyllabic structure and 10 syllable verse. There were isolated instances of verses with schemes of 9 and 13 syllables. Kolomyykovyy 14 syllable verse with scheme of 8,6,8,6 and syllabic verse of 13 syllables with two patterns of the scheme – 8,5,8,5, and 7,6,7,6 dominated the segment of polymetric syllabic-numerical structures (71 % of total amount of syllabic texts of the given time interval). The authors also resorted to syllabic verse of 12 syllables with schemes of 8, 4, 8, 4 and 9, 3, 9, 3; 15 syllables with scheme 8, 7, 8, 7 and 9 syllables with schemes 5, 4, 5, 4. The poet also resorted to non-regulated polysyllable verses.
Syllabic Forms in Works of East Ukrainian Poets of 1890 s.
Keywords: версифікація; силабіка; метрика; ритм; віршовий розмір; клаузула; versification; syllabics; metrics; rhythm; metre; clause